Monitoring neuromuscular fatigue in team-sport athletes using a cycle-ergometer test - Wehbe, G.; Gabbett, T. J.; Dwyer, D.; McLellan, C.; Coad, S. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To compare a novel sprint test on a cycle ergometer with a countermovement-jump (CMJ) test for monitoring neuromuscular fatigue after Australian rules football match play. Methods: Twelve elite under-18 Australian rules football players (mean ± SD age 17.5 ± 0.6 y, stature 184.7 ± 8.8 cm, body mass 75.3 ± 7.8 kg) from an Australian Football League club`s Academy program performed a short sprint test on a cycle ergometer along with a single CMJ test 1 h prematch and 1, 24, and 48 h postmatch. The cycle-ergometer sprint test involved a standardized warm-up, a maximal 6-s sprint, a 1-min active recovery, and a 2nd maximal 6-s sprint, with the highest power output of the 2 sprints recorded as peak power (PP). Results: There were small to moderate differences between postmatch changes in cycle-ergometer PP and CMJ PP at 1 (ES = 0.49), 24 (ES = -0.85), and 48 h postmatch (ES = 0.44). There was a substantial reduction in cycle-ergometer PP at 24 h postmatch (ES = -0.40) compared with 1 h prematch. Conclusions: The cycle-ergometer sprint test described in this study offers a novel method of neuromuscular-fatigue monitoring in team-sport athletes and specifically quantifies the concentric component of the fatigue-induced decrement of force production in muscle, which may be overlooked by a CMJ test.